PENGARUH DIGITAL MARKETING TERHADAP OMSET PENJUALAN PADA PT. KUSUMAHADI SANTOSA DI KARANGANYAR - Prapti estrini (Universitas Sahid Surakarta, 2019)
This research aims to examine the P.T. Kusumahadi Santosa in Karanganyar. P.T. Kusumahadi Santosa to market its products with the digital marketing. This research processed data by using test SPSS regression with multiple linear 22.0. The hypothesis of this research is: ( 1 ) due to allegedly there an effect to a business turnover of digital marketing of goods sold in the pt.Kusumahadi karanganyar santosa said here, (2) Allegedly there is the influence of digital marketing against sales at PT Kusumahadi Santosa Karanganyar, (3) Allegedly there is the influence of digital marketing against sales at PT Kusumahadi Santosa Karanganyar. F test results retrieved value 4.917. The magnitude of the correlation between digitalmarketing with sales turnover is of 0, 267. The results of marketing of digital thitung 2,217. Marketing strategies P.T. Kusumahadi Santosa in Karanganyar in order to achieve sales turnover is by way of digital marketing. The benefits of this study is to find the influence of digital marketing against a business turnover of sales in markets better for you products on P.T. Kusumahadi Santosa said here.